2022
DOI: 10.3389/fgene.2021.814131
|View full text |Cite
|
Sign up to set email alerts
|

The Scope of Pathogenic ABCA4 Mutations Targetable by CRISPR DNA Base Editing Systems—A Systematic Review

Abstract: Stargardt macular dystrophy (STGD1) is the most common form of inherited childhood blindness worldwide and for which no current treatments exist. It is an autosomal recessive disease caused by mutations in ABCA4. To date, a variety of gene supplementation approaches have been tested to create a therapy, with some reaching clinical trials. New technologies, such as CRISPR-Cas based editing systems, provide an exciting frontier for addressing genetic disease by allowing targeted DNA or RNA base editing of pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(126 reference statements)
1
4
0
Order By: Relevance
“…Judging solely on the variant type, base editing appears to be a very promising treatment option for RHO -associated adRP: the majority of pathogenic or likely pathogenic variants could be edited with either an ABE, CBE or GBE ( Figure 5 a)—and, as described above, the majority of the most common disease-associated variants are editable. Of the different base editors, the ABE was the most commonly required construct to correct RHO -variants—similar to what has previously been observed for pathogenic CRB1 [ 34 ] and ABCA4 [ 35 ] variants. The C-to-T transition variants are particularly common in the human genome, as cytosines and 5-methylcytosines are spontaneously deaminated into uracils and thymines, respectively, with an estimated occurrence of 100–500 times per cell per day [ 15 , 36 ].…”
Section: Discussionsupporting
confidence: 68%
“…Judging solely on the variant type, base editing appears to be a very promising treatment option for RHO -associated adRP: the majority of pathogenic or likely pathogenic variants could be edited with either an ABE, CBE or GBE ( Figure 5 a)—and, as described above, the majority of the most common disease-associated variants are editable. Of the different base editors, the ABE was the most commonly required construct to correct RHO -variants—similar to what has previously been observed for pathogenic CRB1 [ 34 ] and ABCA4 [ 35 ] variants. The C-to-T transition variants are particularly common in the human genome, as cytosines and 5-methylcytosines are spontaneously deaminated into uracils and thymines, respectively, with an estimated occurrence of 100–500 times per cell per day [ 15 , 36 ].…”
Section: Discussionsupporting
confidence: 68%
“…Recent research has indicated that prime editing is highly effective in correcting mutations in the porcine ABCA4 gene, thus emphasizing the importance of appropriate ngRNA design and offering a promising avenue for treating Stargardt's disease through gene therapy [29]. These studies have provided a clearer understanding of the potential for base editing approaches as gene therapy strategies for Stargardt's disease [46,47].…”
Section: Stargardt's Diseasementioning
confidence: 99%
“…Stargardt macular dystrophy (STGD1) is the most common form of inherited childhood blindness worldwide with a prevalence of 1 in 8–10,000 individuals [ 48 ]. It is an autosomal recessive disease caused by mutations in ABCA4 , the gene that codes for ATP-binding cassette transporter protein family member 4.…”
Section: Base Editing In Stargardt Macular Dystrophymentioning
confidence: 99%
“…While groups have attempted an AAV dual vector strategy [ 32 ] as used for the LCA preclinical studies described previously, the editing efficiency could be improved by using a single base or prime editor. To look into this approach, Piotter et al screened mutations in three available databases to reveal which of the approximately 1200 known pathogenic mutations in ABCA4 are editable by targeted DNA base editing [ 48 ]. Further studies for the safety and efficacy of this approach are ongoing in the field of ophthalmology, and there is promise for the use of base and prime editing technology to treat this IRD.…”
Section: Base Editing In Stargardt Macular Dystrophymentioning
confidence: 99%